2014
DOI: 10.1002/2014wr015484
|View full text |Cite
|
Sign up to set email alerts
|

Process consistency in models: The importance of system signatures, expert knowledge, and process complexity

Abstract: Hydrological models frequently suffer from limited predictive power despite adequate calibration performances. This can indicate insufficient representations of the underlying processes. Thus, ways are sought to increase model consistency while satisfying the contrasting priorities of increased model complexity and limited equifinality. In this study, the value of a systematic use of hydrological signatures and expert knowledge for increasing model consistency was tested. It was found that a simple conceptual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
252
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 203 publications
(271 citation statements)
references
References 113 publications
8
252
0
Order By: Relevance
“…Result of the recent study by Gao et al (2014) had shown that a more complex, but simultaneously constrained and calibrated model, can provide better predictions of extreme events outside of the calibration period as well as capturing the flow duration curve in nested catchments for the large scale Heihe basin in China. Meanwhile, Hrachowitz et al (2014) reported similar results for a small-scale catchment in France, using 11 different model structures and 20 different runoff signatures. In these studies, the introduction of constraints was found to be crucial for ensuring better model performance, particularly outside of a calibration period.…”
Section: Constraints In Environmental Modelsmentioning
confidence: 79%
See 2 more Smart Citations
“…Result of the recent study by Gao et al (2014) had shown that a more complex, but simultaneously constrained and calibrated model, can provide better predictions of extreme events outside of the calibration period as well as capturing the flow duration curve in nested catchments for the large scale Heihe basin in China. Meanwhile, Hrachowitz et al (2014) reported similar results for a small-scale catchment in France, using 11 different model structures and 20 different runoff signatures. In these studies, the introduction of constraints was found to be crucial for ensuring better model performance, particularly outside of a calibration period.…”
Section: Constraints In Environmental Modelsmentioning
confidence: 79%
“…The multi-objective approach seeks to identify parameter sets that simultaneously provide optimal performance for different aspects of system response (Gupta et al, 1998;Boyle et al, 2000Boyle et al, , 2001. This can include constraining the model to reproduce multiple system fluxes and state variables such as runoff, evaporation, groundwater levels or tracer concentrations (e.g., Gupta et al, 1999;Bastidas et al, 1999;Freer et al, 2002;McDonnell, 2002, 2013;Khu and Madsen, 2005;Fenicia et al, 2008;Winsemius et al, 2008;Birkel et al, 2011;Hrachowitz et al, 2013).…”
Section: S Gharari Et Al: Constraint-based Parameter Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…7a) were used to define 21 different river discharge signatures that cover a range of temporal scales and flow magnitudes. The majority of these signatures were based on previous studies (Coxon et al, 2014;Yilmaz et al, 2008;Westerberg et al, 2016;Shafii and Tolson, 2015;Hrachowitz et al, 2014;Schaefli, 2016;Viglione et al, 2013;Euser et al, 2013;Garavaglia et al, 2017;Yadav et al, 2007;Casper et al, 2012; (99-66% flow exceedance), high flow section (15-5% flow exceedance) and highest flow section (5-0.5% flow exceedance).…”
Section: River Discharge 15mentioning
confidence: 99%
“…autocorrelation) of flows. They have shown to have more discrimination power than traditional error metrics (Hrachowitz et al, 2014;Shafii and Tolson, 2015;Euser et al, 2013;Schaefli, 2016) and, importantly, it is also possible to take account of their information content (i.e. their uncertainty) so that decisions about model appropriateness can 10 be made within the uncertainties of observation data used to evaluate the model.…”
mentioning
confidence: 99%